Nanofiltration - Akhyar Farrukh, Muhammad (IntechOpen, 2018)
The nanofiltration technique lies between ultrafiltration and reverse osmosis techniques, and it is considered a low-cost process and is capable of removing pesticides, organic matter, desalination of sea water, oil process and pollutants from industrial wastewater. However, the main challenge in implementation of nanofiltration membrane is its ability towards fouling and low performance at high temperature. The use of nanoparticles in the manufacturing of membranes allows for a high degree of control over membrane fouling. Nanoparticle-based membranes can be developed by assembling engineered nanoparticles into porous membranes or blending them with polymeric or inorganic membranes. This book covers topics from multiple ranges from manufacturing of nanofiltration membranes and their applications in wastewater treatment, drinking water treatment, and removal of pollutants, to addressing the fouling issues.